2021
DOI: 10.3389/fcvm.2021.741351
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Admission Serological Indicators for Predicting 28-Day Mortality in Intensive Care Patients With Acute Heart Failure: Construction and Validation of a Nomogram

Abstract: Background: Acute heart failure (AHF) is a severe clinical syndrome characterized as rapid onset or worsening of symptoms of chronic heart failure (CHF). Risk stratification for patients with AHF in the intensive care unit (ICU) may help clinicians to predict the 28-day mortality risk in this subpopulation and further raise the quality of care.Methods: We retrospectively reviewed and analyzed the demographic characteristics and serological indicators of patients with AHF in the Medical Information Mart for Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Among the remaining 4,979 papers, a series of publications unrelated to heart failure research, such as conference studies and case reports, were excluded, and 131 articles were obtained. A re-screening of data types and outcome indicators of blood urine nitrogen was performed on the 131 articles, and 19 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) of them were finally included (Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Among the remaining 4,979 papers, a series of publications unrelated to heart failure research, such as conference studies and case reports, were excluded, and 131 articles were obtained. A re-screening of data types and outcome indicators of blood urine nitrogen was performed on the 131 articles, and 19 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) of them were finally included (Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…BNP and NT-proBNP have similar prognostic value in chronic HF on the level of mortality (all-cause, cardiovascular, HF mortality) [ 64 ] and HF-related hospitalization [ 65 ]. Serum troponin T levels can also serve for the early prediction of short-term outcomes such as 28-day mortality in acute HF [ 66 ]. In the context of chronic HF, hs-cTnT strongly predicts mortality (all-cause and cardiovascular), in addition to cardiovascular-related hospitalization [ 67 , 68 ].…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…Some studies reported that demographic information (age), clinical manifestations (NYHA functional class, SBP, DBP, and MAP), pre‐existing conditions (diabetes mellitus and AF), medications (vasopressors), laboratory tests (NT‐proBNP, haemoglobin, sodium, albumin, creatinine, blood urea nitrogen, and eGFR), and 12‐lead resting ECG (RBBB) were significantly associated with OS 8,9,37–40 . However, in the other studies, there was no apparent association of demographic information (age), clinical manifestations (SBP and DBP), pre‐existing conditions (AF), medications, and laboratory tests (NT‐proBNP, haemoglobin, sodium, and creatinine) with long‐term survival 41–43 . To our knowledge, this study is the first risk stratification model to consider including VHD, CRT, and indicators of SPECT MPI (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,37-40 However, in the other studies, there was no apparent association of demographic information (age), clinical manifestations (SBP and DBP), pre-existing conditions (AF), medications, and laboratory tests (NT-proBNP, haemoglobin, sodium, and creatinine) with long-term survival. [41][42][43] To our knowledge, this study is the first risk stratification model to consider including VHD, CRT, and indicators of SPECT MPI (i.e. rest scar burden) to predict the prognosis of AHF.…”
Section: Discussionmentioning
confidence: 99%